(3GSJQGJjLjGJ GdJWhjQ aj GdeDSSGJ GdYQHjI (B/s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2006)
(3GdGOGQI GdGSJQGJjLjI ddeDSSGJ GdJYdjejI, CKQ JcfhdhLjG GdGJUGdGJ hGdeYdheGJ Ydi GdJYdje heLGdGJ GdYed heJWdHGJ GdGSJYOGO ddGdajI GdKGdKI, GdOQhS GdNUhUjI hLg ddGbJUGO GdNaj jYWd GSJQGJjLjGJ GdJYdje, GSJQGJjLjI Jehjd GdJYdje GdLGeYj aj GdGQOf(B: (3GdeTGcd hGdMdhd GdebJQMI, GdJYdje GdYGdj aj Gdjef(B: (3GdhGbY hGSJTQGa GdeSJbHd, GSJTQGa eSJbHd GdJYdje aj GdHdOGf GdYQHjI(B: (3Odjd ebJQM dJehjd GdJYdje GdYGdj, GdCOhGQ hGdbOQGJ GdeYQajI hOhQgG aj JejjR GdbjGOI GdCcGOjejI, GSJQGJjLjGJ GdJWhjQ aj GdJYdje GdYGdj, GYGOI GNJQGY GdLGeYI, GSJQGJjLjI GdJMhd Gdi LGeYI QbejI, bjGS GdOGaY GdeYQaj dOi WdHI LGeYI GdehUd, GdJNWjW GdGSJQGJjLj hGSJbdGdjI GdLGeYIs
Keywords: (3GdEOGQI GdJYdjejI s; (3GdESJQGJjLjIs; (3GdLGeYGJ hGdcdjGJ(B- (3JfXje hEOGQI s